Broadband and highly sensitive comb-assisted cavity ring down spectroscopy of CO near 1.57 µm with sub-MHz frequency accuracy. (March 2015) - Mondelain, D.; Sala, T.; Kassi, S.; Romanini, D.; Marangoni, M.; Campargue, A.
Abstract: A self-referenced frequency comb has been combined with a cavity ring down (CRD) spectrometer to achieve a sub-MHz accuracy on the derived positions of the absorption lines. The frequency emitted by the distributed feedback (DFB) laser diode used in the spectrometer was obtained from the frequency of its beat note with the closest mode of the frequency comb. This delivers excellent frequency accuracy over a broad spectral region with sensitivity (noise equivalent absorption) of 1×10 –11  cm −1  Hz −1/2 . This setup is used to measure the absorption spectrum of CO over a wide range corresponding to the 3–0 band (6172.5–6418.0 cm −1 ). Accurate values of line centers are measured for a total of 184 lines of four CO isotopologues, namely 12 C 16 O, 13 C 16 O, 12 C 18 O and 12 C 17 O present in "natural" abundances in our sample. The measurements include the first extensive study of the 3–0 band of 12 C 18 O and 12 C 17 O, of the 4–1 hot band of 12 C 16 O and the detection of new high- J transitions of the 3–0 band of 12 C 16 O up to J =34. The line centers were corrected for the self-pressure shift and used to derive the upper state spectroscopic parameters. The obtained standard deviation of about 300 kHz and 500 kHz for the 3–0 band of 12 C 16 O and of the minor isotopologues, respectively, is a good estimate of the average accuracy of the reported line centers. The resulting 3–0 line list of 12 C 16 O provided asSupplementary material includes 69 reference line positions with a 300 kHz accuracy for the 6183–6418 cm −1 region. Highlights: A self-referenced frequency comb is combined with a cavity ring down spectrometer. The noise equivalent absorption of the CRDS spectra is α min ≈5×10 −11  cm −1 . The 3–0 band is recorded for four CO isotopologues between 6170 and 6420 cm −1 . 184 Line positions are measured with accuracy better than 500 kHz. Accurate parameters are derived for the v =3 upper state.